Integration of continuous lumbar drainage and third-generation EGFR-TKI in managing leptomeningeal metastasis-induced life-threatening intracranial hypertension: a case report - Wang, Lei; Ren, Nianjun; Tang, Zhi; Wang, Rui; He, Zhengwen (Frontiers in Oncology, 2025)
Leptomeningeal metastasis (LM) from lung cancer carries an extremely poor prognosis, with patients often presenting severe intracranial hypertension symptoms such as intractable headache and recurrent vomiting. Ventriculoperitoneal (VP) shunt placement is commonly used to manage intracranial hypertension in leptomeningeal metastasis but carries risks such as infection, shunt malfunction, tumor seeding, abdominal adhesions, or overdrainage. For patients with suspected EGFR L858R/T790M mutations, lumbar cistern drainage offers a safer alternative by draining cerebrospinal fluid (CSF), reducing intracranial pressure (ICP), and preventing sudden death from critical ICP elevation. This approach also provides a critical therapeutic window for EGFR-TKI therapy. Compared to VP shunts, lumbar cistern drainage is preferred due to its minimally invasive nature, fewer procedural complications, and avoidance of general anesthesia. This study reports a case of EGFR L858R/T790M mutation-positive lung adenocarcinoma with LM and life-threatening intracranial hypertension that achieved marked clinical improvement through combined lumbar drainage and furmonertinib therapy. The approach not only facilitated rapid symptom relief and molecular confirmation of EGFR mutation but also enabled sustained disease control.